2003
DOI: 10.1096/fj.03-0078fje
|View full text |Cite
|
Sign up to set email alerts
|

The importance of propargylamine moiety in the anti‐ Parkinson drug rasagiline and its derivatives for MAPK‐ dependent amyloid precursor protein processing

Abstract: Rasagiline [N-propargyl-(1R)-aminoindan] a highly potent selective irreversible monoamine oxidase (MAO)-B inhibitor exerts neuroprotective and antiapoptotic effects against a variety of insults in cell cultures and in vivo and has finished its phase III clinical trials for Parkinson's disease. In the present study, we show that rasagiline (1 and 10 microM) significantly protected rat PC12 cells against beta-amyloid (Abeta1-42) toxicity. In addition, rasagiline significantly increased (approximately threefold) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 40 publications
9
67
0
Order By: Relevance
“…The activation of proÀsurvival PKC isoforms associated with BclÀ2 family members, the MAPK pathway and induction of neuroptrophic factors by rasagiline and its propargyl moiety [18,44,45] are novel mechanisms of action, which are currently considered in developing new neuroprotective drugs that address multiple central nervous system etiological targets associated with neuropsychiatric disorders [46]. The recent studies demonstrating a neuronal restoration of synaptic transmission in brains of PD animal model, suggest a possible diseaseÀmodifying activity of rasagiline [5].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of proÀsurvival PKC isoforms associated with BclÀ2 family members, the MAPK pathway and induction of neuroptrophic factors by rasagiline and its propargyl moiety [18,44,45] are novel mechanisms of action, which are currently considered in developing new neuroprotective drugs that address multiple central nervous system etiological targets associated with neuropsychiatric disorders [46]. The recent studies demonstrating a neuronal restoration of synaptic transmission in brains of PD animal model, suggest a possible diseaseÀmodifying activity of rasagiline [5].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly we have recently shown that PKC and MAPK pathways may be involved in the enhancement of sAPPα release by ladostigil (Yogev-Falach et al, 2002). However, the effect dose not appear to result from its ChE inhibitiory activity, since rasagiline and N-propargylamine, which do not inhibit ChE, were also able to induce PKC and ERK activation and promote sAPPα release (Yogev-Falach et al, 2003).…”
Section: Molecular Mechanism Of Ladostigil: Neuroprotective Neuroresmentioning
confidence: 95%
“…18,20 Similarly, GF109203X, and the extracellular signal-regulated kinase (ERK)1/ERK2 inhibitor (PD98059) prevented rasagiline activation/phosphorylation of p42 and p44 mitogen-activated protein kinase (MAPK), thus indicating that rasagiline directly activates PKC-MAPK pathway. 22 The importance of PKC pathway in rasagiline-and propargylamine-induced neuroprotective activity is supported also by previous data demonstrating that these compounds 20,22 induced the release of the neuroprotective-neurotrophic nonamyloidogenic soluble amyloid precursor protein ␣ (sAPP␣) by MAPK-and PKC-dependent mechanisms in vitro. 18 -21 Current therapeutic approaches suggest that drugs acting at a single target may be insufficient for the treatment of multifactorial neurodegenerative diseases such as PD, Alzheimer's disease (AD), Huntington's disease (HD) and amyotrophic lateral sclerosis (ALS), all characterized by the coexistence of multiple etiopathologies.…”
Section: Introductionmentioning
confidence: 64%
“…However, this neuroprotective effect of ladostigil does not appear to result from its ChE inhibition activity only, since rasagiline or propargylamine were also able to induce PKC and ERK activation and promote sAPP␣ release. 22 Several ChEIs, such as tacrine, 80 physostigmine, 81 metrifonate, 82 ganstigmine, 83 and donepezil 84 increased sAPP␣ release in cell culture. However, the observations that phenserine 78 and tacrine, at high concentration, 85 decreased sAPP␣ release suggests that the regulation of APP processing by ChEIs is not simply associated to AChE inhibition.…”
Section: Neuroprotective Mechanisms Of Action Of Ladostigilmentioning
confidence: 99%